2012
DOI: 10.3109/10717544.2012.721144
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled pyrazinamide proliposome for targeting alveolar macrophages

Abstract: We suggest that PZA-proliposomes are potential candidates for pulmonary tuberculosis treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(34 citation statements)
references
References 22 publications
1
31
0
2
Order By: Relevance
“…Permeability determination of AmB (white square), AmB-KDC (black triangle), AmB-SDC (black square), AmB-SDCS (white triangle), and AmB-SC (black circle) from 15 to 120 min, respectively (mean±SD, n=3) 600 nm were efficiently phagocytosed and, in our case, nanoparticle sizes of <100 nm were efficiently phagocytosed (25). A similar result was reported by Rojanarat et al (26). These results supported the view that AmB-SDCS lipid formulation was phagocytosed by AM NR8383 cells.…”
Section: Phagocytosis Of Anti-fungal Reconstituted Dry Powder Particlsupporting
confidence: 77%
“…Permeability determination of AmB (white square), AmB-KDC (black triangle), AmB-SDC (black square), AmB-SDCS (white triangle), and AmB-SC (black circle) from 15 to 120 min, respectively (mean±SD, n=3) 600 nm were efficiently phagocytosed and, in our case, nanoparticle sizes of <100 nm were efficiently phagocytosed (25). A similar result was reported by Rojanarat et al (26). These results supported the view that AmB-SDCS lipid formulation was phagocytosed by AM NR8383 cells.…”
Section: Phagocytosis Of Anti-fungal Reconstituted Dry Powder Particlsupporting
confidence: 77%
“…Results of in vivo toxicity studies showed that capreomycin oleate exhibited its lowest toxic potential suggesting it be used as super generics in pulmonary tuberculosis treatment [73]. Outcomes of various miscellaneous lipid based drug delivery systems in the treatment of TB are summarized in Table 6 [74][75][76][77][78][79][80][81][82][83][84][85][86].…”
Section: Miscellaneous Lipid Based Formulationsmentioning
confidence: 99%
“…8,10,[21][22][23] The adjusted doses of the four drugs are 2-7 times of the calculated doses according to different drug potency (2-16 mg). These were done to compromise the feasible fixed dose combination of anti-TB for inhalation which should not be too high or too low.…”
Section: )mentioning
confidence: 99%
“…The dry powder formulations used in this study were formulated using liposomal-based drug delivery systems to target the alveolar macrophages. 7,8,10,19) …”
mentioning
confidence: 99%
See 1 more Smart Citation